PENGARUH KUALITAS PRODUK, HARGA, DAN LOKASI TERHADAP LOYALITAS DENGAN KEPUASAN DAN CITRA SEBAGAI VARIABEL MEDIASI PADA KONSUMEN RUMAH MAKAN DAPUR SOLO - Mahendra, Denny; Haryanto, Aris Tri (Jurnal Bulletin, 2017)
The Influence of Product Quality, Price, and Location on Loyalty with Satisfaction and Image as Mediation Variable on Consumen Solo Restaurant. To know consumer attitudes toward their products, companies need to conduct research on the factors contained in these products that can encourage the creation of a buying motive. By analyzing consumer responses to product quality, price, location, image and loyalty, the company can assess which factors are not in accordance with the wishes and needs of consumers. Based on this research, this study aims to determine the effect of product quality, price, and location on loyalty with satisfaction and image as a mediation variable in Solo restaurant customers. The sample taken in this study is 20% of the population of 200 consumers. By random sampling technique by random. Analytical technique using path analysis. The results showed that product quality significantly influenced consumer satisfaction. Price has a significant effect on customer satisfaction. Location has no significant effect on customer satisfaction. Product quality has a significant effect on image. Price has significant effect on image. Location has significant effect on image. Product quality significantly influences consumer loyalty. Price has a significant effect on loyalty. Location has a significant effect on loyalty. Satisfaction has a significant effect on loyalty. The image has a significant effect on the results of path analysis shows that: The use of intervening satisfaction for product quality variables on loyalty is effective and the image intervening is not effective. The use of satisfaction and image intervening for price variables on loyalty is ineffective. The use of satisfaction and image intervening for location variables is effective